Cristóbal Suárez de Figueroa, Author of The Second Quixote. A Critical Analysis of a Candidacy - O´Kuinghttons Rodríguez, John (2021)
This article aims at making a critical review of the candidacy of Cristóbal Suárez de Figueroa as one of the possible authors of Avellaneda’s Quixote. To accomplish this goal, we will compare the arguments presented by Enrique Espín and Enrique Suárez Figaredo, the most important advocates of this candidature, focusing specifically on the texts that defend this candidacy. Firstly, we will give an overview of what we know about Avellaneda. Secondly, we will concentrate on the origin and development of Figueroa’s candidacy. Finally, we will reflect on how the research about Avellaneda’s identity can guide us on the knowledge of the Golden Age’s artistic context, when we take the name of Suárez Figueroa as the starting point of the study. To develop this study, we will also refer to the state of the research methods on the field of authorship attribution as far as Avellaneda´s Quixote is concerned